A Bibliometric Analysis of Green Investment Trends and Developments - Judijanto, Loso; Praja, Selvia Junita; Arini, Rani Eka (West Science Social and Humanities Studies, 2024)
This study presents a bibliometric analysis of green investment research, examining its trends, thematic focus, and developments from 2000 to 2024 using data from Scopus and Web of Science. The analysis reveals that foundational topics such as energy production, cost management, and process efficiency dominate the field, while recent research emphasizes green finance, technological innovation, and regional development. Key drivers include regulatory frameworks, technological advancements, and evolving financial mechanisms, while barriers such as regional disparities, limited sectoral representation, and inconsistent sustainability metrics persist. Emerging themes like digital technologies, R&D investment, and supply chain sustainability highlight opportunities for future research and innovation. The findings emphasize the need for interdisciplinary approaches and policy interventions to address gaps and scale green investments globally. This study provides actionable insights for researchers, policymakers, and practitioners, contributing to the discourse on sustainability and the strategic role of green investment in achieving global environmental goals.